Fuel cell bipolar plate coating material with high corrosion resistance and high conductivity characteristics and coating method

By using adhesive resin and carbon material filler coatings on fuel cell separators, the problem of reduced conductivity of the separator in corrosive environments is solved, and a high corrosion resistance and low cost coating method is achieved, which is suitable for a variety of applications. Application scenario.

CN119325655APending Publication Date: 2025-01-17HYUNDAE STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202280096857.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-07
Filing Date
2022-11-03
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The problem of fuel cell separators with reduced conductivity in corrosive environments is that traditional coating processes are costly and difficult to be applied to lightweight materials such as titanium and their alloys.

Method used

Using a coating composed of adhesive resin and filler, the filler contains sheet and granular carbon materials, a highly conductive coating is formed by thermal curing and brushing techniques, the filler is exposed to the coating surface to improve conductivity and through orientation Filling to reduce surface resistance.

Benefits of technology

A diaphragm with high corrosion resistance and high conductivity is achieved, reducing costs, PEMFC diaphragm suitable for automotive, aviation and fixed equipment, and expanding the selection range of diaphragm materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119325655A_ABST
    Figure CN119325655A_ABST
Patent Text Reader

Abstract

The present invention relates to a fuel cell bipolar plate and a fuel cell bipolar plate coating method, the fuel cell bipolar plate having corrosion resistance and high conductivity, and provides a fuel cell bipolar plate comprising: a metal substrate; and a coating layer formed on the metal substrate and composed of a mixture of a binder resin and a filler, the filler including a sheet-like carbon material and a particulate carbon material, in which the filler is surrounded by the binder resin so that the filler is dispersed inside the coating layer, and the filler is exposed to the outside on a surface of the coating layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a fuel cell metal diaphragm coating material and a fuel cell metal diaphragm coating method capable of suppressing surface corrosion while ensuring electrical conductivity. Background Art

[0002] Recently, in order to cope with global warming, there has been an increase in demand for electric vehicles (EV) or hydrogen fuel cell electric vehicles (FCEV) to replace internal combustion engines (ICE). Among them, hydrogen fuel cell electric vehicles have a chemical reaction opposite to electrolysis. In other words, it is a power generation system that generates electricity (and heat) to drive a motor by supplying hydrogen. Theoretically, a hydrogen fuel cell can generate a voltage of 1.229V, but due to various limitations, its operating voltage is 0.6V to 0.8V. A hydrogen fuel cell stack includes a bipolar plate, a gas diffusion layer (GDL), and a membrane electrode assembly (MEA) coated with catalyst powder.

[0003] The redox reaction equations of the fuel cell are shown in (1) and (2).

[0004] (Hydrogen supply) H2→2H + +2e - E 0 =0V vs SHE Electrochemical oxidation of hydrogen (hydrogen oxidation reaction, HOR)... (1)

[0005] (Oxygen supply) 1 / 2O2+2H + +2e - →H2O E 0 =1.229V vs SHE Electrochemical reduction of oxygen (oxygen reduction reaction, ORR)… (2)

[0006] In addition to the high potential environment, the corrosion environment in the fuel cell is also a highly corrosive environment due to the low pH, as shown in reaction equations (3) to (8). Free radicals are generated by the reduction of the metal (Equations 3 and 4), and SO4 is generated by the degradation of the sulfonyl and CF groups of the resin. 2- and F - (Fenton reaction) (Reaction equations 5 to 8).

[0007] Fe 2+ +H2O2→Fe 3+ + OH+OH - …(3)

[0008] Fe 3+ +H2O2→Fe 2+ +·OOH+H + …(4)

[0009] R-SO4+·OH or ·OOH→ROH+SO4 2- …(5)→2H2O+SO4 2- →

[0010] 2H + +SO4 2- +2OH - …(6)

[0011] RC-F+·OH or ·OOH→RC-OH+F - …(7) → H2O + F - →H + +F - +OH - … (8)

[0013] The separator is a key component that connects multiple unit cells and forms the frame of the battery stack, and requires a material that can withstand a pH of 4 or higher. Even in actual corrosion testing, experiments are conducted in an environment of pH 1 to 3 and 0.6 to 0.0 V vs SCE. In this environment, the material should exhibit 1 μA / cm at a zeta potential of 0.6 V vs SCE. 2 or less current density and 10mΩcm 2 Or less interface contact resistance (under a pressure of 133N / m). In addition, the material is required to have a conductivity of 100S / cm or more, and metal materials show a high initial conductivity of 104S / cm or more, but there is a problem of reduced conductivity due to corrosion.

[0014] Titanium metal has excellent electrical conductivity, but in a corrosive environment, a TiO2 layer with a thickness of about 200 nm is formed on the surface layer of the titanium metal, which is much larger than the passivation film (5 nm) of stainless steel such as CrO3 or Cr3O7 in stainless steel, so it needs to be controlled (see Figure 4 ). In other words, the partially passivated growth film of the stainless steel series is not suitable for lightweight materials such as Ti, Al and Mg. Conventional thin film coatings such as physical vapor deposition (PVD) and chemical vapor deposition (CVD) are limited in application due to coating time and economic issues. In addition, the thin film coating disclosed in Japanese Patent No. 06943781 is applied by a vacuum high temperature process, which is difficult to apply easily. Summary of the invention

[0015] Technical issues

[0016] The present invention is directed to solving such conventional problems, and an object of the present invention is to provide a fuel cell membrane having high resistance to permeation by external materials, thereby suppressing surface corrosion and ensuring electrical conductivity. However, these challenges are exemplary, and the scope of the present invention is not limited thereto.

[0017] Technical Solution

[0018] According to one aspect of the present invention, a fuel cell membrane is provided.

[0019] In one embodiment, a fuel cell membrane includes a metal substrate and a coating, wherein the coating is formed on the metal substrate and is composed of a mixture of a binder resin and a filler, wherein the filler includes a flaky carbon material and a granular carbon material, wherein the filler is surrounded by the binder resin so that the filler is dispersed inside the coating and the filler is exposed to the outside on the surface of the coating.

[0020] In one embodiment, the filler may also include metal powder.

[0021] In one embodiment, the filler may be at least one selected from graphene, carbon nanotubes, graphite, and carbon black.

[0022] In one embodiment, the coating may have a thickness of 0.01 μm to 10 μm.

[0023] In one embodiment, the density of the filler in the coating may be 10 EA / cm 2 Up to 10 4 EA / cm 2 .

[0024] In one embodiment, the filler may be arranged at an angle of 30 to 90 degrees relative to the surface of the substrate.

[0025] In one embodiment, the metal substrate may be formed of titanium or a titanium alloy.

[0026] In one embodiment, the binder resin may be a linear or branched polymer.

[0027] In one embodiment, the metal powder may be stainless steel powder.

[0028] According to another aspect of the present invention, a fuel cell membrane coating method is provided.

[0029] In one embodiment, a fuel cell membrane coating method includes: mixing 10 wt % to 70 wt % of a binder resin and 30 wt % to 90 wt % of a filler comprising a flaky carbon material and a granular carbon material, applying the mixture on a substrate and thermally curing it, and brushing the surface of the cured substrate, wherein the flaky carbon material and the granular carbon material can be mixed with each other in a weight ratio of 7:3 to 8:2.

[0030] In one embodiment, the filler may further include metal powder, and 60 to 80 wt % of the flaky carbon material, 20 to 30 wt % of the granular carbon material, and 0.01 to 10 wt % of the metal powder may be mixed with each other.

[0031] In one embodiment, the filler may be at least one selected from graphene, carbon nanotubes, graphite, and carbon black.

[0032] In one embodiment, the substrate may be formed of titanium or a titanium alloy.

[0033] In one embodiment, the binder resin may be a linear or branched polymer.

[0034] In one embodiment, the metal powder may be stainless steel powder.

[0035] Beneficial Effects

[0036] According to the embodiments of the present invention as described above, the durability of the cell stack is improved by providing a diaphragm having high corrosion resistance and high conductivity. In addition, by providing a coating type coating method, it is possible to replace the existing vapor deposition type coating and electroplating type coating, and cost effectiveness is ensured compared to the existing methods. In addition, it can be applied to PEMFC diaphragm coatings for automobiles, aviation, and stationary equipment, and has the effect of expanding the range of diaphragm material selection.

[0037] Of course, this effect does not limit the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 is a schematic diagram showing the structure of a coating layer according to one embodiment of the present invention.

[0039] Figure 2 is a schematic diagram showing the state of a filler in a coating layer according to an embodiment of the present invention.

[0040] Figure 3 is a graph comparing the performance of a battery stack according to the type of metal substrate in one embodiment of the present invention.

[0041] Figure 4are photographs comparing the corrosion environment after heat treatment according to the type of metal substrate in one embodiment of the present invention. DETAILED DESCRIPTION

[0042] Hereinafter, various embodiments of the present invention will be described in detail with reference to the attached drawings. The embodiments of the present invention are intended to provide a more complete description of the present invention to those skilled in the art, and the following embodiments may be modified in a variety of other forms, and the scope of the present invention is not limited to the following embodiments. On the contrary, these embodiments are provided to provide a more thorough and complete disclosure and to fully convey the ideas of the present invention to those skilled in the art. In addition, for the convenience and clarity of description, the thickness or size of each layer in the drawings has been exaggerated.

[0043] Figure 1 A fuel cell membrane according to one embodiment of the present invention is shown.

[0044] exist Figure 1 In the embodiment, a coating is formed on a metal substrate 10, wherein the coating is composed of a mixture of a binder resin 20 and a filler 30, wherein the filler 30 includes a flaky carbon material 32 and a granular carbon material 31. The coating can be formed by applying a composition mixed with 10 wt % to 70 wt % of the binder resin 20 and 30 wt % to 90 wt % of the filler 30 including the flaky carbon material and the granular carbon material on the substrate. The method of applying the composition may include, but is not limited to, a pre-coating method, a nano spray method, and the like.

[0045] The binder resin 20 is used to bind the filler 30 composed of the carbon material, and is an important factor in determining the properties of the coating. If the content of the binder resin is higher than 70 wt%, the surface resistance is too high, and if the content of the binder resin is lower than 10 wt%, the mechanical properties of the coating may not be ensured. Therefore, it is preferred to mix the binder resin in a ratio of 10 wt% to 70 wt%.

[0046] The types of the adhesive resin 20 may include, but are not limited to, conventional resins (e.g., polyacrylic resins, polyphenol resins, and polyester resins) and conductive resins (e.g., polyaniline, polyphenylene sulfide (PPS), and polyacetylene). The adhesive resin composition may be blended with various components such as solvents, curing agents, pigments, pigment dispersants, additives, etc. The adhesive resin composition may further include a polymerization initiator (e.g., a thermal initiator, a photoinitiator, etc.) to promote polymerization.

[0047] The adhesive resin 20 can be prepared by subjecting the adhesive resin composition as described above to a thermal curing or photocuring process. For example, the curing reaction can be a solid phase reaction (solid polymerization) using a blocked isocyanate. When the blocking agent (e.g., ketone, alcohol, etc.) dissociates, a curing reaction can occur. In the case of a thermal curing reaction, the reaction can be carried out at 20°C to 250°C. After curing, the adhesive resin 20 can have a temperature of 10°C to 250°C. -4 Conductivities in the range of S / cm to 10 S / cm.

[0048] The binder resin can be a linear or branched polymer. The more branched the polymer is, the higher the corrosion resistance is, but there is a trade-off of lower conductivity. Therefore, in embodiments of the present invention, linear polymers can be used, but branched polymers can also be appropriately mixed and used. For example, branches can be introduced by grafting monomers onto a linear polymer backbone.

[0049] The molecular weight and viscosity of the binder resin 20 can be adjusted so that the binder resin 20 uniformly surrounds the filler, so that the filler exists in a uniformly dispersed state without settling. The dispersibility of the filler is important for determining the conductivity of the separator, and therefore, the filler must be uniformly dispersed in the binder resin. As the molecular weight of the binder resin increases, the viscosity of the mixture increases, and therefore, it is desirable to adjust the molecular weight of the binder resin between 100MW and 5000MW.

[0050] In the case of an organic coating type coating, the corrosion resistance is excellent, but the resistance is high due to the poor resistance of the resin and the connectivity of the conductive filler. Therefore, in an embodiment of the present invention, a mixture of an adhesive resin and a filler is applied to a substrate and then thermally cured to reduce the thickness of the coating by thermal shrinkage so that the fillers can adhere to each other. The thickness of the coating may be 10 μm or less to suppress the increase in resistance caused by the increase in the thickness of the coating.

[0051] It is important to adjust the type and orientation of filler 30 to reduce the surface resistance of the diaphragm. Filler 30 can be composed of carbon materials, such as graphene, carbon nanotubes (CNT), graphite and carbon black, and if necessary, can also contain metal powder. The shape of the filler may affect the formation of the network for electron transport. In one embodiment, highly conductive flake graphene and carbon nanotubes can be used to form a needle-like or sheet-like structure to achieve multi-point surface contact.

[0052] Granular graphite or carbon black may be mixed to prevent the flaky carbon materials from being separated from each other due to the binder resin, thereby causing a decrease in conductivity. The granular carbon material may be partially inserted into the surface of the flaky carbon material and used to reduce the distance between the flaky carbon materials, thereby forming a network path for electron transport. Here, the flaky carbon material and the granular carbon material may be mixed in a weight ratio of 7:3 to 8:2.

[0053] In another embodiment, the filler may further comprise metal powder to improve the electrical conductivity of the filler. The metal powder may be, but is not limited to, stainless steel or a noble metal series. For example, the electrical conductivity of the filler may be improved by mixing 60 wt % to 80 wt % of a flaky carbon material, 20 wt % to 30 wt % of a granular carbon material, and 0.01 wt % to 10 wt % of a metal powder.

[0054] In order to reduce the surface resistance of the diaphragm, relative to the surface of the metal substrate 10, the flaky carbon material constituting the filler 30 can be oriented at an angle of 30 to 90 degrees, more preferably 40 to 90 degrees. If the filler is randomly arranged or oriented at a low angle, the current may become uneven, and the current may be partially interrupted by the polymer resin with insulating properties, thereby causing the contact resistance to increase and the conductivity to decrease. In one embodiment, it may further include coating the composition comprising the filler on the substrate, and then orienting the filler so that it is tilted at an angle of 30 ° or more. For example, during the coating process, a magnetic field generator or an electric field generator may be connected to a coating machine to generate a magnetic field or an electric field around the filler so that the direction of the filler is aligned, or a physical force may be applied to the coating so that the filler is oriented to 30 ° or more. This enables the current in the coating to be smoothly controlled.

[0055] In one embodiment, the density of the filler may be 10 EA / cm 2 Up to 10 4 EA / cm 2 , more preferably 100EA / cm 2 Up to 10 4 EA / cm 2 , thereby achieving high conductivity and low contact resistance. The viscosity of the carbon material or the paste mixed with the carbon material and the metal can be 10 3 S / cm to 10 4 S / cm.

[0056] The fuel cell membrane manufactured according to the embodiment of the present invention can exhibit an electrical conductivity of 500 S / cm or more and can have an electrical conductivity of 35 mΩ / cm without applying pressure. 2 or less contact resistance value, when applying 133N / cm 2 The pressure can be 5mΩ / cm 2or smaller contact resistance value.

[0057] The amount of filler mixed with the binder resin is preferably 30% to 90% by weight. If the content of the filler is less than 30% by weight, it is difficult to expect improvement in conductivity because a network path for electron transport cannot be formed. If the content of the filler exceeds 90% by weight, the dispersibility and molding processability of the filler are poor.

[0058] Figure 2 2 is a schematic diagram showing brushing the surface of the coating to expose the filler. By removing the binder resin surrounding the filler on the surface of the coating, the filler can be exposed to the outside. For example, the number of brushing times can be 300 to 2000 times. Figure 2 (a) shows that the filler is exposed to the surface of the coating by brushing, and the conductivity is improved. Figure 2 (b) shows that a part of the binder resin located in the outermost layer is removed by removing a part of the coating, thereby increasing the filler area. Therefore, the filler is surrounded by the binder resin, so that the filler is dispersed inside the coating and the filler is exposed to the outside on the surface of the coating.

[0059] The metal substrate 10 may be formed of titanium or a titanium alloy. Titanium (Ti) material is more expensive than stainless steel material, but can exhibit higher battery stack performance. Using the same membrane electrode assembly (MEA) and at 1A / cm 2 The absolute performance (power) of the stainless steel and Ti diaphragms at current densities is Figure 3 As shown in . After 100 cycles, stainless steel has an output of 0.6897 and Ti has an output of 0.8379, which shows the excellent durability of the titanium material. In addition, stainless steel has a specific gravity of 7.9, while Ti has a lower specific gravity of 4.6, resulting in a weight reduction of 40% or more when applied with the same thickness.

[0060] As described above, the fuel cell separator according to the embodiment of the present invention may have excellent corrosion resistance, low contact resistance, and excellent electrical conductivity.

[0061] The present invention has been described with reference to the embodiments shown in the accompanying drawings, but these are exemplary only, and those skilled in the art will appreciate that various modifications and other equivalent embodiments are possible. Therefore, the true technical protection scope of the present invention should be determined by the technical ideas of the attached patent claims.

[0062] (Explanation of Reference Numerals)

[0063] 10: Metal substrate

[0064] 20: Adhesive resin

[0065] 30: Filling

[0066] 31: Granular carbon material

[0067] 32: Flake carbon material

[0068] Industrial Applicability

[0069] The present invention can be used in the fields of fuel cells, fuel cell metal diaphragms, and metal diaphragm coatings and coating materials, and can improve the reliability and competitiveness of products.

Claims

1. A fuel cell membrane, comprising: metal substrate; and a coating layer formed on the metal substrate and composed of a mixture of a binder resin and a filler, the filler comprising a flaky carbon material and a granular carbon material, wherein the filler is surrounded by the binder resin so that the filler is dispersed inside the coating layer, and The filler is exposed to the outside on the surface of the coating layer.

2. The fuel cell membrane according to claim 1, wherein: The filler also includes metal powder.

3. The fuel cell membrane according to claim 1, wherein: The filler is at least one selected from graphene, carbon nanotubes, graphite and carbon black.

4. The fuel cell membrane according to claim 1, wherein: The coating has a thickness of 0.01 μm to 10 μm.

5. The fuel cell membrane according to claim 1, wherein: The density of the filler in the coating is 10 EA / cm 2 Up to 10 4 EA / cm 2 .

6. The fuel cell membrane according to claim 1, wherein: The filler is arranged at an angle of 30° to 90° relative to the surface of the substrate.

7. The fuel cell membrane according to claim 1, wherein: The metal substrate is formed of titanium or a titanium alloy.

8. The fuel cell membrane according to claim 1, wherein: The binder resin is a linear or branched polymer.

9. The fuel cell membrane according to claim 2, wherein: The metal powder is stainless steel powder.

10. A fuel cell membrane coating method, the fuel cell membrane coating method comprising: mixing 10 to 70 wt % of a binder resin and 30 to 90 wt % of a filler consisting of a flaky carbon material and a granular carbon material; applying the mixture to a substrate and thermally curing it; as well as brushing the surface of the cured coating on the substrate to expose the filler on the surface of the coating to the outside; The flaky carbon material and the granular carbon material are mixed with each other in a weight ratio of 7:3 to 8:

2.

11. The fuel cell membrane coating method according to claim 10, wherein: The filler further includes metal powder, and 60 to 80 wt % of the flaky carbon material, 20 to 30 wt % of the granular carbon material, and 0.01 to 10 wt % of the metal powder are mixed with each other.

12. The fuel cell membrane coating method according to claim 10, wherein: The filler is at least one selected from graphene, carbon nanotubes, graphite and carbon black.

13. The fuel cell membrane coating method according to claim 10, wherein: The substrate is formed of titanium or a titanium alloy.

14. The fuel cell membrane coating method according to claim 10, wherein: The binder resin is a linear or branched polymer.

15. The fuel cell membrane coating method according to claim 11, wherein: The metal powder is stainless steel powder.